A Study of Fiqh Al-Muwatanah Juz 1 and 2 and Its Relationship to Muslim and Non-Muslim Relations in Indonesia - Husaeri, Rifki Ahmad; Shahruddin, Mohd Solahuddin (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2026)
This study explores the dynamics of relations between Muslims and non-Muslims in Indonesia through the study of the Fiqh Al-Muwatanah book, written by alumni of the Lirboyo Islamic Boarding School in Kediri, as a response to the challenges of nationality, plurality, and religiosity. The study highlights the transformation of classical Islamic jurisprudence (fiqh) views regarding the status of non-Muslims, replacing the term "kafir" with the concept of non-Muslims as equals (muwatin), which is relevant to the life of the modern nation-state. The study uses a qualitative descriptive-analytical method with document studies, critical textual studies, and a contextual approach to understand the principles of citizenship, tolerance, and social integration. The results show that Islam Nusantara emphasizes ukhuwah wathaniyah (brotherhood), unity of the ummah, and acceptance of pluralism, placing social welfare above differences in fiqh methodology or minor creeds. This principle is realized through respect for the government, the prohibition of rebellion, the ethics of enjoining good and forbidding evil, and gradual and contextual da'wah (preaching). This approach emphasizes equality of citizenship, protection of basic rights, and recognition of social and religious diversity, without sacrificing the principles of creed. The study also emphasizes that Islam is a mercy for all the worlds, guiding people to act justly, be caring, and maintain social and ecosystem balance. The historical context, including colonialism, classical fiqh, and the experience of the Indonesian archipelago as Darul Islam, demonstrates the need to reinterpret classical norms within the framework of ethics, pluralism, and human rights. Thus, Fiqh Al-Muwatanah offers moderate and inclusive guidance, strengthening social cohesion, affirming the role of active citizens, and building peace in a pluralistic society, making Islamic practice contextual, peaceful, and relevant to modern Indonesia.